Sobre a atividade da consciência infeliz na Fenomenologia do Espírito de Hegel - Machado, Aline Eduardo (2013)
We carried out an analysis of the Unhappy Consciousness (unglücklichesBewusstsein), such expounded by G.W.F.Hegel in his 1807 publication Phenomenology of Spirit (Phänomenologie des Geistes). Unhappy consciousness is a Hegelian term referring to religious consciousness that is divided into two: on one of its halves, it is alienated from itself, and its essence — the immutable — dwells beyond; the other half, itself, is asserted by the mutable, the -un-essence?, which dwells here.All its activity is summarized into uniting what is proposed as infinitely disunited to knowledge, and consciousness to its essence; because consciousness is not yet aware that this absolute essence it opposed to itself is nothing but itself. This results in a single trend towards the absolute universal object which, at the same time, does not aim at maculating it with its singularity; in an activity that should absolutely be and not to be, it searches for something that neither can nor should be sought. As heir of stoic and skeptical thought, unhappy consciousness appears as contradictory consciousness, bending over itself and constantly sore, which besides realizing a movement of denial towards the world of here and all it concerns, it seeks to get rid of the pain inherent to this inconsistency that emerges exactly from its negative attitude. In order to provide grounds for this unhappy attitude, our first chapter of investigations is carried out on peculiar characteristics of spheres prior to its rise, i.e. sphere of Understanding (Verstand), Master-Slave dialectic and Stoicism and Skepticism dialectic. In the second chapter, we discuss the concept and activity of unhappy consciousness, and also investigate the need of overcoming it based on analyses of its suppression at the moment of Reason (Vernunft).Finally, in our third chapter, we seek to reflect on to what extent it would be possible to say that contemporary consciousness continues to operate in an unhappy way. For this purpose, we find basis on short readings of S. Freud — the modern "illness" thinker, and Z. Bauman — contemporary -illness? thinker.